Flaps and Trills in Najdi and Hijazi Arabic - Alrasheedi, Eisa S. (International Journal of Linguistics, 2022)
This study is an investigation of flaps and trills in Najdi and Hijazi Arabic, which are the most spoken Arabic varieties in Saudi Arabia. It focuses on how flaps and trills behave in relation to vowels and consonants in the two varieties of Arabic. The data in this study were collected from four Hijazi and five Najdi participants. A total number of 730 sentences were read by the participants. It was found that /r/, which is the underlying phoneme, surfaces as [r] when it occurs word-initially or after a [-coronal] consonant, a [+voiced] consonant, or a [-coronal, +voiced] consonant, otherwise /r/ surfaces as [ɾ]. In Najdi Arabic, /ɾ/, which is the underlying phoneme, surfaces as [r] after a [-coronal, +voiced] consonant; otherwise /ɾ/ surfaces as [ɾ] elsewhere. Also, it was found that Najdi Arabic violates the sonority hierarchy, as in [ɾtaʕ] and [batɾ], in which the segments in the onset of [ɾtaʕ] and the coda of [batɾ] do not maintain the universal sonority hierarchy: glides>liquids>nasals>obstruents, which is maintained in Hijazi Arabic. This paper argues that rhotics in both varieties of Arabic may be sensitive to the preceding adjacent consonants, but not to vowels.